Hakikat Pendidikan IPA - Ar Rizky Maulana Akbar; Aura Khairunnisa; Indah Puspita Sari; M Rifqy Atsir; Raihan Chandra Gumelar; Wibisono F Budiargo; Wati Sukmawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Science Education (IPA) has a very important role in the development of science, technology, and in forming critical and analytical thinking patterns of students. Through science learning, students not only gain knowledge about scientific concepts, but are also trained to think critically, systematically, and creatively in dealing with various problems. One aspect that influences the success of science learning is cognitive psychology, which focuses on how individuals process, store, and remember information. Cognitive psychology plays an important role in designing effective learning strategies, which are tailored to the way students understand and manage information. In addition, the learning paradigm used in science education also greatly influences the success of learning. The two main paradigms that are widely considered in science learning are absolutism and constructivism. The absolutism paradigm argues that knowledge is absolute and must be accepted without change, while the constructivism paradigm assumes that knowledge is built through experience and active interaction with the environment. This article aims to explore how the tradition of cognitive psychology influences science learning and examines the differences in the impact of the two paradigms in the context of science education in Indonesia. This discussion is expected to provide a deeper understanding of the importance of applying cognitive psychology and selecting the right learning paradigm in improving the quality of science education.